PENGARUH KUALITAS LAYANAN DAN KEWIRANIAGAAN TERHADAP KEPUASAN NASABAH KREDIT PENSIUN SERTA DAMPAKNYA PADA LOYALITAS NASABAH - Maman Sulaeman; Sri Sudiarti; Sri Mulyati; Dedeh Sundarsih; Devy Kustantini (Jurnal Aplikasi Bisnis, 2018)
Feedback from customers on the quality of services that have been given a reference in evaluating the ability of a Bank in creating customer satisfaction. The research method used in this study was survey method. The data collected by questionair and literature study. The population in this research were the pensions who have credit of pension at Bank Saudara 1906, Tbk branch Tasikmalaya. The determination of sample was based on the analyze variable amount and determined as many as 100 persons. The data analysis used path analysis. The research concluded that service quality and salesmanship was positive significant influented on consumer satisfaction. Simultaneously or partial of service quality and salesmanship was positive significant influent on Customer Loyalty. Customer Satisfaction was positive significant influent on Customer Loyalty. So the hypothesis is verified.